Evading the Patronage Trap - Palmer-Rubin, Brian (University of Michigan Press, 2022)
Why have Latin American democracies proven unable to confront the structural inequalities that cripple their economies and stymie social mobility? Brian Palmer-Rubin contends that we may lay the blame on these countries’ systems of interest representation, which exhibit “biased pluralism,” a system in which the demands of organizations representing economic elites—especially large corporations—predominate. A more inclusive model of representation would not only require a more encompassing and empowered set of institutions to represent workers, but would also feature spaces for non-eliteproducers—such as farmers and small-business owners to have a say in sectoral economic policies.